Expert System to Diagnose Problems Acne Whitening Method Using the Base Case Reasioning - Mulyana, Sri Ulina; Panggabean, Erwin (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Lack of knowledge about the problem of acne for the people who do not know how to prevent early steps to prevent acne more inflamed. This system can help doctors to facilitate patient diagnosis and can save the patient's medical records for consideration of the results of diagnoses of new problems that will come. Therefore, this study aims to produce an expert system for diagnosing acne problems on the face using the case base reasoning method. The algorithm used for the CBR method is the Nearest Neighbor Retrieval algorithm for determining the value of disease symptom weighting based on: if the symptoms of the selected disease will be the same value of 1 and if the symptoms chosen are not the same will be value of 0 to the symptoms of old disease cases. In this CBR method the system will determine the solution of the problem with the highest level of similarity value which will be chosen as the solution of the new problem.